(untitled) (Gaceta Técnica, 2014)
The purpose of this article is to determine the environmental proactivity incidence on economic-financial, environmental and operating performance of non-metallic mining (gravel) companies in Lara State. Environmental proactivity consists of strategies and actions a company performs beyond environmental laws. The sample consisted of eight (8) companies, which represents 50% of the non-metallic mining sector population. A questionnaire using a Likert scale was applied, distinguishing between the reactive and proactive environmental management orientation (Aragón 1996). The results show an environmental proactivity of the sector leaders, in regulatory aspects (correlation 0.71) Environmental Objectives (correlation 0.96) and Monitoring and Control (correlation 0, 98). One positive correlation between the environmental profile of the companies under study with the economic and financial performance (correlation 0.51) and operational performance (0.70) but environmental performance was different (-042). It concluded that the results should be studied in depth through an environmental audit